Time- and concentration-dependent cytotoxicity of antibiotics used in endodontic therapy - Marina Beloti Ferreira; Suely Myiagi; Carlos Goes Nogales; Marcia Sampaio Campos; José Luiz Lage-Marques (University of São Paulo, 2010)
OBJECTIVE: New drugs have to be assessed in endodontic therapy due to the presence of microorganisms resistant to therapeutic procedures. Thus, this study evaluated the time- and concentration-dependent cytotoxicity of different antibiotics used in endodontic therapy. MATERIAL AND METHODS: Human gingival fibroblasts were treated and divided into the following experimental groups: Group I - control; Group II - ciprofoxacin hydrochloride; Group III - clyndamicin hydrochloride; and Group IV - metronidazole. Each drug was used at concentrations of 5, 50, 150, and 300 mg/L for 24, 48, 72, and 96 h. Cytotoxicity was evaluated by the MTT assay [3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide] and spectrophotometric reading of ELISA plates. The results were analyzed by BioEstat 4.0 software using Kruskal-Wallis and Dunn's tests at a signifcance level of 5%. Cell viability was assessed for the different concentrations and times. RESULTS: All drugs presented dose-dependent cytotoxicity. Concentrations of 5 and 50 mgjL produced viable fibroblasts at all experimental times in all groups. CONCLUSIONS: Cell viability at 24 h was greater than in the other experimental times. Comparison between the same concentrations of antibiotics at different times showed that metronidazole presented the highest cell viability at 72 and 96 h compared to the other antibiotics, whereas clyndamicin hydrochloride showed higher cell viability at 72 h than ciprofoxacin hydrochloride.